The pests of grain of spiked cultures during storage - Bondarenko, I.V.; Sekun, N.P.; Vlasova, O.G. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2016)
The results of monitoring of species composition and relative quantity insects and mites — pests and polluters of grain of spiked cultures during storage were presented. Detected 80 species of insects and mites, which belong to two classes, 7 orders and 30 families. The dominant species among them were identified. It was agreed, that level of occupancy and contamination of grain related to the temperature and moisture of environment, grain and stored culture.